Single‐dose evaluation of safety, tolerability and pharmacokinetics of newly formulated hydromorphone immediate‐release and hydrophilic matrix extended‐release tablets in healthy Japanese subjects without co‐administration of an opioid antagonist. (6th May 2015) - Toyama, Kaoru; Uchida, Naoki; Ishizuka, Hitoshi; Sambe, Takehiko; Kobayashi, Shinichi
Abstract This single dose, open‐label study investigated the safety, tolerability and pharmacokinetics of single oral doses of newly formulated immediate‐release (IR) and hydrophilic matrix extended‐release (ER) hydromorphone tablets in healthy Japanese subjects without co‐administration of an opioid antagonist under fasting and fed conditions. Plasma and urinary concentrations of hydromorphone and metabolites were measured by liquid‐chromatography tandem mass‐spectroscopy. Following administration of the ER tablet, plasma concentrations of hydromorphone slowly increased with a median tmax of 5.0 h and the Cmax decreased to 37% of the IR tablet, while the AUC0‐inf was comparable with that of the IR tablet when administered at the same dose. The degree of fluctuation in the plasma concentration for the ER tablet was much lower than that of the IR tablet and certain levels of plasma concentrations were maintained after 24 h of ER dosing. The AUC0‐inf and Cmax increased with food for both IR and ER tablets. The AUC0‐inf of hydromorphone‐3‐glucoside was one‐tenth of that of hydromorphone‐3‐glucuronide. A single oral administration of the hydromorphone tablets would be well‐tolerated in healthy Japanese subjects despite a lack of co‐administration of an opioid antagonist and the newly developed ER hydromorphone tablets may have the appropriate PK characteristics for once‐daily dosing.